Implementation of Collaborative Market-Driving Strategies in Destination Tourism - Abeykoon, Herman Mahendra; Karlíček, Miroslav, 1979-; Kottika, Efthymia, 1982-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Abstract Traditional market-driven strategies, which are often reactive to consumer demands and competitive dynamics, frequently fail to address the complexities of destination tourism collaborations. This study explores the implementation and integration of collaborative market-driving strategies within destination tourism with a specific focus on Sri Lanka's tea tourism sector, a niche characterized by experiential tourism and sustainable growth. A Systematic Literature Review of over 250 scholarly works establishes the conceptual foundation, while a qualitative inductive case study methodology gathers field data through 23 semi-structured interviews with industry experts across eight tea tourism destinations in Sri Lanka. The qualitative inductive approach is complemented by observations and document analysis, ensuring a holistic understanding of these strategies. The research identifies a structured five-stage framework—Formation, Mobilization, Transformation, Integration, and Monitoring & Adaptation—that guides the implementation of collaborative market-driving strategies. Findings highlight how peer collaboration, supra firms, and transformational leadership play critical roles in overcoming challenges such as trust deficits, stakeholder fragmentation, and resource inefficiencies. Additionally, this study emphasizes the proactive role of market-driving strategies in reshaping industry structures and demand by integrating new industry players and redefining traditional tea plantations as tourism destinations. A key insight is the emergence of social enterprises as transformative agents that balance economic, social, and environmental objectives, moving beyond profit maximization to emphasize equitable value distribution, cultural preservation, and ecological sustainability.
Furthermore, by integrating Collaborative Market-Driving Strategies with Common-Pool Resource (CPR) Theory, this research offers a transformative framework for shared resource management and social cohesion, advocating for partnership-based approaches that align collective goals with economic viability and cultural heritage preservation. The findings advance theoretical understanding, refine existing frameworks, and offer actionable insights for destination tourism stakeholders. By shaping markets rather than merely responding to them, collaborative market-driving strategies enhance sector resilience, competitiveness, and long-term sustainability.
Vedoucí práce: Miroslav Karlíček
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management and managerial economics [obor disert. práce]; disertace; dissertations